Predictors of Malignancy in Branch Duct Intraductal Papillary Mucinous Neoplasm of the Pancreas - Kawada, Natsuko; Uehara, Hiroyuki; Nagata, Shigenori; Tsuchishima, Mutsumi; Tsutsumi, Mikihiro; Tomita, Yasuhiko (JOP. Journal of the Pancreas, 2014)
Objective Indication of surgery for branch duct intraductal papillary mucinous neoplasm (BD-IPMN) proposed by the consensus guidelines revised in 2012 was too complex to refer to in clinical practice. This study aimed to identify simple predictors of malignancy in BD-IPMN. Methods Consecutive 202 patients with BD-IPMNs were enrolled. They comprised 35 patients that underwent surgery and 167 that were followed up without surgery by being regarded as benign neoplasms. Cutoff values of cyst size, main pancreatic duct (MPD) diameter, and mural nodule size were determined by receiver operator characteristic (ROC) curve. Factors that may discriminate benign from malignant BD-IPMNs were analyzed by multivariate logistic regression model. Results Cutoff values of cyst size, MPD diameter, and mural nodule size were determined to be 30 mm, 6 mm, and 10 mm, respectively. Multivariate analysis demonstrated that mural nodule ≥10 mm (OR 198, 95% CI 23.1-1690, P<0.0001) and positive cytology (OR 634, 95% CI 49.1-8,190, P<0.0001) were predictors of malignancy in BD-IPMN. When BD-IPMNs with mural nodules ≥10 mm or positive cytology were diagnosed as malignant, sensitivity, specificity, and overall accuracy were 88%, 98%, and 97%, respectively. Conclusions Mural nodule ≥10mm and positive cytology were demonstrated to be simple predictors of malignancy in BD-IPMN. Image: ROC curves of cyst size, main pancreatic duct diameter, and nodule size.